2005
DOI: 10.1044/1092-4388(2005/061)
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Processing Continuum of Single-Word Comprehension in Aphasia

Abstract: This study investigated the vulnerability of lexical processing in individuals with aphasia. Though classical teaching of aphasia syndromes holds that people with Broca's aphasia have intact comprehension at the single-word level, the nature and extent of this purported sparing were explored under suboptimal processing conditions. A combination of acoustic distortions (low-pass filtering and time compression) was used to probe for "break points" in lexical comprehension in a group of individuals with aphasia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 30 publications
1
43
2
Order By: Relevance
“…However, although our work demonstrates the tight coupling between auditory and articulatory information, it does not allow us to conclude that motor processes are required in speech perception [as in single-pathway architectures in which motor representations mediate the acoustic and linguistic processing of speech (17,18)]. Such inferences about causality can be drawn conclusively only by studying speech perception in situations in which motor processes are impaired through temporary lesions [as in TMS (5, 6)] or as a result of brain injury (19,20). However, further work establishing the temporal character of motor activation in speech perception could also be important in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…However, although our work demonstrates the tight coupling between auditory and articulatory information, it does not allow us to conclude that motor processes are required in speech perception [as in single-pathway architectures in which motor representations mediate the acoustic and linguistic processing of speech (17,18)]. Such inferences about causality can be drawn conclusively only by studying speech perception in situations in which motor processes are impaired through temporary lesions [as in TMS (5, 6)] or as a result of brain injury (19,20). However, further work establishing the temporal character of motor activation in speech perception could also be important in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a neuroimaging study revealed that, during an /r/ versus /l/ consonant identification task, Broca's area was more activated in Japanese speakers whose mother tongue did not differentiate the two consonant sounds than in native English speakers (Callan et al, 2004). Motor systems may also contribute to perception in adverse listening circumstances, as evidenced by the specific perceptual difficulty patients with Broca's aphasia experience when speech signals are degraded (Utman et al, 2001;Moineau et al, 2005). The current findings lend further support to the theory that auditory and motor systems interact during speech perception.…”
Section: Possible Roles Of Broca's Area In Speech Perceptionmentioning
confidence: 99%
“…Moineau, Dronkers, & Bates, 2005;Utman, Blumstein, & Sullivan, 2001), or from studies in which TMS is used to transiently interfere with neural processes in motor regions (D'Ausilio, 2007;Meister, Wilson, Deblieck, Wu, & Iacoboni, 2007;Mottonen & Watkins, 2009). We note with interest, however, that all these studies show modulation of perception of speech that has been degraded*either by artificial speech manipulations (D'Ausilio, 2007;Meister et al, 2007;Moineau et al, 2005) or by the use of phonemically ambiguous materials (Mottonen & Watkins, 2009;Utman et al, 2001). These studies, therefore, converge with our fMRI work in suggesting that motor responses to speech are more likely of functional significance in listening situations in which the perception of speech is challenged by noise or phonetic ambiguity.…”
Section: Motor-cortical Responses To Degraded Speechmentioning
confidence: 99%